Clinico-epidemiological pattern of pityriasis versicolor in Sudanese patients at Khartoum dermatology and venerology hospital, Khartoum State, Sudan, 2012-2013 - Mohammed, Otarid Bashir; Alla, Khalid Badreldin Fadl (International Journal of Research in Dermatology, 2023)
Background: Pityriasis versicolor is a fungal skin disease, chronic and superficial in the course, characterized by skin pigmentary changes that psychologically impact the patient’s quality of life. This paper intended to determine the clinico-epidemiological pattern of the Pityriasis versicolor in patients who attended the outpatient clinic of Khartoum dermatology teaching hospital (KDTH) from June 2012 to February 2013. Method: This descriptive, analytical, cross-sectional hospital-based study used a quantitative method. A total convenient sample technique enrolled 110 patients during the study period. Results: The 30.9% of the participants were between 11 and 20 years old, 67.3% were males, and 37.1% were of low socioeconomic status, 47.2% had a family history of the disease, 68.1% had first-degree relatives, 56.4% and 60% had a history of a similar condition in the summer, respectively. 57.3% were originally from a pure Arab tribe, compared to 0.9% from purely African tribes. There were significant associations between being male with a positive family history, the onset of the disease, color of the lesions, and having disease (p=0.02, 0.05, 0.04, respectively). Also, between the age with a history of similar condition and the associated symptoms (p=0.00 and 0.03 respectively). Conclusions: Most participants were young males who had the disease in the summer with a high recurrence rate. There were multiple significant associations between gender and age with some clinical and epidemiological patterns. Determining any genetic association with pityriasis versicolor, improving counselling, and raising awareness to understand age the predisposing factors were recommended in this paper.